2021
DOI: 10.1590/1678-4324-75years-2021210140
|View full text |Cite
|
Sign up to set email alerts
|

Integration of a Pilot PV Parking Lot and an Electric Vehicle in a University Campus Located in Curitiba: a Study Case

Abstract: Considering the increasing adoption of Hybrid Plug-in and Electric Cars, there are concerns about recharging process of these vehicles considering the capacity of grid to provide sufficient energy to that purpose. In the past years, the growth of distributed energy generation from renewable and clean energy sources, especially photovoltaics, represents a possible and feasible solution to supply the energy used on recharging electric vehicles and reduction of greenhouse emission gases as CO2. This article is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Table 5 displays the PBP for several projects utilizing PV-powered EV charging systems. In the identical scenario, this resulted in a different PBP solely because of the alteration in the price of the energy unit (electricity or fossil fuel) as documented by Kulik et al [41,42]. The typical PBP ranged from 1 to 15 years.…”
Section: Economic Metrics For Evcss Powered By Solar or Wind Energymentioning
confidence: 94%
See 3 more Smart Citations
“…Table 5 displays the PBP for several projects utilizing PV-powered EV charging systems. In the identical scenario, this resulted in a different PBP solely because of the alteration in the price of the energy unit (electricity or fossil fuel) as documented by Kulik et al [41,42]. The typical PBP ranged from 1 to 15 years.…”
Section: Economic Metrics For Evcss Powered By Solar or Wind Energymentioning
confidence: 94%
“…If 15% of the fleet is replaced with EVs, 17,151.8 MWh of electricity would need to be generated, requiring the construction of 36,856 carports, totaling around 1,105,685 square meters. Kulik et al [42] showed that a solar carport system may effectively fulfill the energy needs for EV usage. The carport may generate an average of 483 kWh per month.…”
Section: Case Studies On Solar-powered Ev Charging Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…The environmental degradation resulting from greenhouse gas emissions and the upcoming shortage of fossil fuels highlights the importance of generating energy with minimal environmental impacts, confirming the relevance of including different energy sources in the national energy matrix [1][2][3].…”
Section: Introductionmentioning
confidence: 91%